ANALISIS KATA SERAPAN BAHASA ARAB BERDASARKAN PEMBENTUKAN KATA BAHASA MELAYU - Zaidan, Noor Azlina; Abd Rahman, Mohd Zaki; Zailaini, Muhammad Azhar (Jurnal Pengajian Melayu (JOMAS), 2018)
This article discusses Arabic loanwords in Malay word formation (in Jawi script), especially singular words. The data in the form of Arabic loanwords were derived from the text books of Islamic Education Primary School, Years 1 to 6 (KSSR). Arabic loanwords were analyzed according to the method of Malay word formation (consonant-vowel pattern) by Nik Safiah Karim (2015). In analyzing the Jawi data, the Malay-Jawi-Rumi Glossary (DKBM) was used as a basic reference and guidance for Jawi spelling. The findings indicate that there is diversity in the pattern of vowel-consonant combination of Arabic loanwords in the Malay language. Most of the consonant-vowel patterns of the Arabic loanwords are not found among pure Malay words. The study of Arabic loanword analysis based on Malay word formation is a pioneering study of Arabic loanwords in Malay in terms of how it analyses comparative patterns of vowels-consonants between the two languages, and broadens the study of Malay language word formation and general knowledge of Malay grammar. Keywords: Arabic loanwords, word formation, Malay, pattern vowelconsonant.